THE COMPETITIVE DEMANDS OF ELITE MALE RINK HOCKEY - Aladino Fernández; Vesa Linnamo; Jorge Egocheaga; Miguel Enrique Del Valle; Pablo Luis Yagüe (Termedia Publishing House, 2013)
The aim of this study was to simulate the activity pattern of rink hockey by designing a specific skate test (ST) to study the energy expenditure and metabolic responses to this intermittent high-intensity exercise and extrapolate the results from the test to competition. Six rink hockey players performed, in three phases, the 20-metre multi-stage shuttle roller skate test, a tournament match and the ST. Heart rate was monitored in all three phases. Blood lactate, oxygen consumption, ventilation and respiratory exchange ratio were also recorded during the ST. Peak HR was 190.7±7.2 beats · min-1. There were no differences in peak HR between the three tests. Mean HR was similar between the ST and the match (86% and 87% of HRmax, respectively). Peak and mean ventilation averaged 111.0±8.8 L · min-1 and 70.3±14.0 L · min-1 (60% of VEmax), respectively. VO2max was 56.3±8.4 mL · kg-1 · min-1, and mean oxygen consumption was 40.9±7.9 mL · kg-1 · min-1 (70% of VO2max). Maximum blood lactate concentration was 7.2±1.3 mmol · L-1. ST yielded an energy expenditure of 899.1±232.9 kJ, and energy power was 59.9±15.5 kJ · min-1. These findings suggest that the ST is suitable for estimating the physiological demands of competitive rink hockey, which places a heavy demand on the aerobic and anaerobic systems, and requires high energy consumption.